Performance Comparison of FA, PSO and CS application in SINR Optimisation for LCMV Beamforming Technique - Doroody C.; Kiong T.S. (Springer New York LLC, 2023)
Beamforming; Bioluminescence; Fire protection; MATLAB; Signal interference; Spurious signal noise; Beamforming technique; Firefly algorithms; LCMV; Meta heuristic algorithm; Nature inspired algorithms; Optimisations; Particle swarm optimisation; Performance comparison; Particle swarm optimization (PSO)